The Synergy of Islamic Religious Education and Moral Education in Shaping the Character of Elementary School Students - Putri, Widia; Sujarwo (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Islamic Religious Education and moral education play a strategic role as key pillars in shaping the character of elementary school students to face increasingly complex contemporary challenges. Both function not merely as a transmission of normative knowledge, but also as essential instruments for instilling fundamental values such as honesty, responsibility, and empathy in everyday life. Through a literature-based study reviewing various academic journals and scholarly references, this study finds that the integration of religious and moral education within the formal education system constitutes a crucial foundation for students’ character development. The analysis indicates that strengthening these two aspects in an integrated manner has a significant impact, particularly on improving students’ moral conduct, discipline, and awareness of social responsibility. Therefore, strong synergy is required among educational institutions, the role of teachers as role models, and the family environment as the primary foundation to ensure that moral and spiritual values are optimally internalized in the educational process. Thus, this article emphasizes that Islamic religious and moral education in elementary schools plays an important role in shaping a young generation that is religious, possesses noble character, and is ready to become a pillar of the nation by contributing positively to society and the wider world.